(untitled) (The Shivapuri Journal, 2025)
The illicit arms proliferation is one of the prominent threats to national security not only in Nepal but everywhere in the world. This paper reviews the dynamics of the illegal arms proliferation in Nepal by looking into historical context, current trends, and impact on national security. Using secondary data analysis, contextualized in the regional context of Nepal, this study aims to highlight the illegal arms circulation enhances crime, weakens public safety, and undermines security within the community. The paper will conclude with the recommendations which necessary to deal with the illicit arm proliferation in Nepal.